The effects of inhalation aromatherapy with rose and lavender at week 38 and postpartum period on postpartum depression in high-risk women referred to selected health centers of Yazd, Iran in 2015 - Maryam Kianpour; Fateme Moshirenia; GolamReza Kheirabadi; GolamReza Asghari; Ali Dehghani; Arefah Dehghani-tafti (Wolters Kluwer Medknow Publications, 2018)
Background: Postpartum depression (PPD) is one of the most common problems in women of childbearing age. This study was conducted to evaluate the efficacy of aromatherapy on PPD. Materials and Methods: In this study, 105 pregnant women at 35-37 weeks of pregnancy were enrolled using convenient sampling and randomly assigned to three groups. The intervention group dropped 7 drops of lavender oil and 1 cc rose water at the concentration of 100%, and the placebo group dropped 7 drops of odorless sesame seed oil, with 1 cc of musk willow sweat at the concentration of 100% by dropper on a special cloth. They put the cloths on their mouths and took 10 deep breaths before sleeping and then placed them next to their pillows. The control group only received the routine care. The intervention lasted from 38th week of pregnancy until 6 weeks after delivery. Then depression level was determined before the intervention, 35-37 weeks of pregnancy, 2 and 6 weeks after delivery using Edinburgh questionnaire. Results: The mean of depression score in the intervention group decreased significantly compared to the placebo and control groups, 2 weeks (F = 9.412, p < 0.001) and 6 weeks after delivery (F = 7.813, p < 0.01). Conclusions: This study provides valid evidence for the effect of aromatherapy on PPD. Therefore, the use of aromatherapy can be recommended in high-